Public investment and economic growth in anglophone Caribbean countries - Vital, kent (Caribbean Centre for Monetary Studies [St. Augustine]TT, 2003)
Analyzes the effect of private investment and public investment on economic growth with an empirical model using data covering the period 1988 to 2000.